Implementing epidemic intelligence in the WHO African region for early detection and response to acute public health events. (14th May 2021) - Williams, George Sie; Impouma, Benido; Mboussou, Franck; Lee, Theresa Min-Hyung; Ogundiran, Opeayo; Okot, Charles; Metcalf, Tatiana; Stephen, Mary; Fekadu, Senait Tekeste; Wolfe, Caitlin M.; Farham, Bridget; Hofer, Cristina; et al.
Abstract: Epidemic intelligence activities are undertaken by the WHO Regional Office for Africa to support member states in early detection and response to outbreaks to prevent the international spread of diseases. We reviewed epidemic intelligence activities conducted by the organisation from 2017 to 2020, processes used, key results and how lessons learned can be used to strengthen preparedness, early detection and rapid response to outbreaks that may constitute a public health event of international concern. A total of 415 outbreaks were detected and notified to WHO, using both indicator-based and event-based surveillance. Media monitoring contributed to the initial detection of a quarter of all events reported. The most frequent outbreaks detected were vaccine-preventable diseases, followed by food-and-water-borne diseases, vector-borne diseases and viral haemorrhagic fevers. Rapid risk assessments generated evidence and provided the basis for WHO to trigger operational processes to provide rapid support to member states to respond to outbreaks with a potential for international spread. This is crucial in assisting member states in their obligations under the International Health Regulations (IHR) (2005). Member states in the region require scaled-up support, particularly in preventing recurrent outbreaks of infectious diseases and enhancing their event-based surveillance capacities with automated tools and processes.